The effects of COVID-19 on Central Florida’s community gardens: lessons for promoting food security and overall community wellbeing - Schanbacher, William D.; Cavendish, James C. (Frontiers in Public Health, 2023)
Although public health officials, food systems workers, and food justice scholars and activists have recognized structural problems in the food system for quite some time, the COVID-19 pandemic has highlighted and exacerbated problems related to food insecurity, inequitable access to food, and supply chain deficiencies. During the fall and summer of 2021, the University of South Florida’s Urban Food Sovereignty Group conducted a survey of forty-five leaders of community gardens throughout Central Florida. Drawing on data from that survey, we describe the impact that the pandemic has had on the community gardens in this region. Results reveal that during the pandemic community gardens intensified their efforts to provide more fresh food to pantries and traditional emergency food outlets. While some gardens were able to maintain their regular operations and reported that membership or participation in their garden actually increased during the pandemic, most gardens were forced to change their routines in various ways, such as limiting the number of workers and volunteers, or changing the mode of communication and delivery of workshops and education programs. Because survey respondents also shared the lessons they learned during the pandemic, we conclude by offering several suggestions for how community gardens might respond to similar circumstances in the future -- ways that will ensure food security, but ultimately cultivate the community ties necessary for food sovereignty.